Traditional Food Wrapping And Packaging : Culture And Identity Of The Saribas Malay, Sarawak - Faridah, Sahari; Rahah, Hasan; Anna, Durin; Shahren, Ahmad Zaidi Adruce; Shahri, Abdul Rahman (2017)
This paper analyses the basic principles of food wrapping and packaging practiced by the Saribas Malay in Sarawak, focusing on the aspect of technology, roles, materials of the traditional means. The main purpose of this study is to discover how this part of the Saribas Malay’s culture, cuisine is interpreted in the form of indigenous scientific knowledge and technology, and art. Interviews and observation wrapping. This little effort and attempt is hoped to conserve the traditional food have been conducted in several villages in Saribas such as Betong, Pusa, Beladin, Debak and Spaoh to gather information and identify individuals with knowledge and skills in food knowledge, the representational of culture and identity of the Saribas Malay.